(untitled) (The Peerian Journal, 2025)
The study aims to examine the relationship between the proactive behavior of university employees and the effectiveness of internal control and audit activities, through analyzing the opinions of a sample of Al-Qasim Green University employees. A descriptive analytical approach was adopted to achieve the study’s objectives, with a questionnaire used as the primary tool for data collection. The results indicated a significant impact of proactive behavior on enhancing the efficiency and effectiveness of control and audit systems, while also offering a set of recommendations to enhance positive organizational behavior. The study concluded that the management of the organization under study lacks a clear interest in encouraging administrative leaders to practice proactive behavior, which is considered an activity that works to seize and anticipate opportunities within the organization in order to maintain the effectiveness of internal control and audit, which entails ambition and the pursuit of excellence in controlling how to change in the future. Furthermore, the management of Al-Qasim Green University should contribute positively to dialogue and cooperation within the educational institution in a manner consistent with work requirements and based on different perspectives.